SIKAP “GOLPUT” MASYARAKAT PADA PEMILIHAN UMUM KEPALA DAERAH GUBERNUR DAN WAKIL GUBERNUR RIAU PUTARAN PERTAMA DI DESA RIDAN PERMAI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR TAHUN 2013 - Rafli Arham; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The high level of "Abstentions" on the implementation of the elections had a warm conversation today. The purpose of this study was to determine the attitude of the form "Abstentions" and factor in the emergence of an attitude "Abstentions" Governor elections in the first round in 2013 in the village Ridan Permai Bangkinang City of Kampar District. This research used descriptive quantitative method. The sampling method that used was "Simple Random Sampling". Obtained a number of 123 respondents. For collecting data, the researcher used interview and documentation, for processing the data using descriptive quantitative method. Results of "Abstentions" in community has the following forms, namely attitude, the attitude of alienation, anomie, cynicism and apathy. The factors that encourage the emergence of an attitude "Abstentions" was a factor instrumental rational action, value of rational action, affective actions, as well as traditional measures. This study concluded that there should the improvement of public confidence towards the implementation of the elections by the committee that the Commission and political parties as participants in the elections, as candidates, leaders of political parties are carried.Keywords: Gubri Elections In 2013